Public policy: a new introduction - Knill, Christoph; Tosun, Jale (Palgrave Macmillan, 2012)
Introduction -- The nature of the public policies -- The context for policy making: central institutions and actors -- Theoretical approaches to policy making -- Problem definition and agenda setting -- Decision making -- Implementation -- Evaluation -- Governance: a synoptic perspective on policy making -- Public policies beyond the nation state -- Policy change and policy convergence -- Conclusions: future challenges for public policy analysis
Literaturverz. S. 295 - 333
Keywords: Lehrbuch; Politische Steuerung; Staatstätigkeit